An Investigation of Tribology Conduct of Alumina Coating on Austenitic Steel - Jeevabharathi, S. (International Journal of Psychosocial Rehabilitation, 2019)
The increasing importance of developments in mechanical industry requires a constant evolution of skills, particularly in the area of functionalization and protection of metal surfaces. In this work, 500 micron-thick Al2O3 coatings were deposited on a substrate made of austenitic steel AISI 316 by thermal spray coating. For the protection against oxidation, Al2O3, which has an excellent ability to hinder the inward diffusion of oxygen, is desired. Especially above 1000 oC, Al2O3 becomes the most effective oxide against environmental attacks. In the experimental testing, the Rockwell hardness of AISI 316 coated with Al2O3 was found to be 27.83 HRC, and in the salt spray test, we noticed that the red rust formation was not found after 12 hours for the coated specimen, and the red rust formation was found after 12 hours for the uncoated specimen.